1989
DOI: 10.1111/j.1471-4159.1989.tb11773.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of σ‐Receptors: High‐ and Low‐Affinity Agonist States, GTP Shifts, and Up‐Regulation by Rimcazole and 1,3‐Di(2‐Tolyl)guanidine

Abstract: The regulation of the central sigma-binding site was investigated using both in vitro and in vivo manipulations in conjunction with radioligand binding. The displacement of the binding of R(+)-[3H]3-[3-hydroxyphenyl]-N-(1-propyl)piperidine [R(+)-[3H]3-PPP] to cortical homogenates by a range of drugs was consistent with the site labelled being a sigma-receptor. (+)-SKF 10,047, (-)-SKF 10,047, (+/-)-cyclazocine, phencyclidine, and dexoxadrol displaced R(+)-[3H]3-PPP with pseudo-Hill coefficients of less than 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

1991
1991
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 54 publications
3
27
1
Order By: Relevance
“…Discussion of data is restricted to an indication of the number of sites and whether ligands have relatively higher or lower affinity. The initial observation which suggested the feasibility of such an approach was that under the conditions used in our experiments, and in contrast to the literature at the time (Weber et al, 1986) (Zhou & Musacchio, 1991;Klein & Musacchio, 1992 RI (Zhou & Musacchio, 1991 (Itzhak, 1989;Beart et al, 1989). Reducing the concentration of [3H]-DTG from 3.4 nM to 0.34 nM resulted in a reduction in labelling of the low affinity site, R4.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Discussion of data is restricted to an indication of the number of sites and whether ligands have relatively higher or lower affinity. The initial observation which suggested the feasibility of such an approach was that under the conditions used in our experiments, and in contrast to the literature at the time (Weber et al, 1986) (Zhou & Musacchio, 1991;Klein & Musacchio, 1992 RI (Zhou & Musacchio, 1991 (Itzhak, 1989;Beart et al, 1989). Reducing the concentration of [3H]-DTG from 3.4 nM to 0.34 nM resulted in a reduction in labelling of the low affinity site, R4.…”
Section: Discussioncontrasting
confidence: 51%
“…It has been suggested that rat brain membranes contain predominantly R3 (Klein & Musacchio, 1991), RI, the other affinity site, being found in much lower density (10%) than in guinea-pig brain membranes. Nevertheless, the use of [3H]-( + )-pentazocine has allowed the presence of al and a2 sites in rat brain to be confirmed (Vilner & Bowen, 1992 (Beart et al, 1989;Itzhak, 1989 (McCann & Su, 1992). The contribution of interactions at this site have not been addressed by our work and require further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the rank order potency of the compounds tested as antagonists of HVA Ca2" channels (Table 1) does not parallel that of their affinities for high-affinity a binding sites. Thus rimcazole, one of the more potent Ca2" channel blockers tested, is a relatively weak displacer of binding to high-affinity a sites (Ferris et al, 1986;Manallack et al, 1988;Beart et al, 1989;Barnes et al, 1992). Conversely, DTG, (+)-3-PPP, L 687,384 and (+)-pentazocine, which possess high affinities for a sites (Manallack et al, 1988;Beart et al, 1989;Musacchio et al, 1989;Ferris et al, 1991;Middlemiss et al, 1991;Barnes et al, 1992;Cagnotto et al, 1994) Ferris et al, 1991), was only a moderately potent Ca2" channel blocker.…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…1991b; Riviere et al, 1990), suggesting that it might act on sigma receptors. Guanosine triphosphate (GTP)-binding regulatory G proteins (guanine nucleotide-binding proteins) might be involved in the biological effects of several high affinity sigma ligands (Itzhak & Khouri, 1988;Chattarji et al, 1989;Itzhak, 1989). Indeed, in rat brain membrane preparations, GTP and Gpp(NH)p reduce the high affinity component of the binding of the sigma ligands (+ )-N-allylnormetazocine [(+ )-SKF-10,047], ( + )-3-PPP and pentazocine, this phenomenon being attributed to the conversion of sigma receptors from a high to a low affinity state (Irzhak & Khouri, 1988;Beart et al, 1989). As Gpp(NH)p reduces the slower dissociative component of sigma binding, it has been proposed that, in their high affinity state, at least a subpopulation of sigma receptors are coupled to G proteins (Itzhak, 1989 (Itzhak, 1989), suggesting the coupling of sigma receptors to Gi/O proteins (Gilman, 1987;Fredholm & Lindgren, 1988;Hertting & Allgaier, 1988).…”
Section: Introductionmentioning
confidence: 99%